Translation Procedures Used in Medan Heritage and Culinary Tourism Booklet - Desy Dwi Jayanti; Bambang Panca Syahputrara (Britain International for Academic Research (BIAR-Publisher), 2022)
This study deals with Translation Procedures in Medan Heritage and Culinary Tourism Booklet. It was aimed to investigate the kinds of translation procedures in Medan Heritage and Culinary Tourism Booklet, to describe the realization as well as to elaborate the reason translation procedures used in the way they are. This study was conducted by using descriptive qualitative research. The sources of data were taken from the Medan Heritage and Culinary Tourism Booklet 2015. The result showed that there were 135 data found in Medan Heritage and Culinary Tourism Booklet. Specifically 31 (22.96%) for Addition, 4 (2.96%) for Subtraction, 43 (31.85%) for Transposition, 1 (0.74%) for Modulation, 42 (31.10%) for Borrowing, 0 (0%) for The Cultural Equivalent, 1 (0.74%) for Descriptive Equivalent and Componential Analysis, 0 (0%) for Synonym, 5 (3.4%) for Official Translation, 0 (0%) for Depreciation, 0 (0%) The Alliteration of the Clarity Meaning, 6 (4.44%) for Reduction and Expansion, 0 (0%) for The Illocutionary Change, 1 (0.74%) for The Change of Structural Information, 0 (0%) for Partial Translation, Visibility Change, Trans- level Editing, and Adaptation. The dominant procedure used is Transposition. The realization of translation procedures were realized or express into singlet, couplet, triplet and quadruplet-use in of word, phrase, clause or sentence. The total number of singlet-use translation procedure are 120 data (88.89%), the total number of couplet-use are 14data (10.37%), the triplet-use is 1 data (0.74%) and there is no data realized quadruplet-use in the text. The reason of translation procedures used in text were classified into 2 basic tenors namely Domestication and Foreignization. Foreignization is the principle translation procedure that translator choose to be faithful with in translating the text in Medan Heritage and Culinary Tourism Booklet.